Performance evaluation of patch repairs on historic concrete structures (PEPS): a methodology for in situ and laboratory analyses - Wilkie Simeon; Ducasse-Lapeyrusse Jean; Arato Gonçalves Ana Paula; Marie-Victoire Elisabeth; Macdonald Susan; Bouichou Myriam; Lauder Nicki; Farrell David; Gaudette Paul; Harrer Ann (MATEC Web of Conferences, 2022)
While there have been many studies on the performance criteria of concrete patch repairs, there are few specific studies on the long-term performance of patch repairs designed to preserve the aesthetic significance of the original fabric of culturally significant concrete structures. In order to address this issue, the Getty Conservation Institute (GCI), Historic England (HE) and the Laboratoire de Recherche des Monuments Historiques (LRMH) commenced work on an international collaborative research project, ‘Performance Evaluation of Patch Repairs on Historic Concrete Structures’ (PEPS). Begun in 2018, the PEPS project aims to produce practical guidance that will help those repairing historic concrete through the assessment of case studies in the USA, England and France within a variety of climatic and environmental conditions, typologies and repair materials. The operational phases of the research project consist of in situ tests and laboratory analysis performed on both the original concrete and previous patch repairs. This paper provides an overview of the assessment methodology that has been developed by an inter-disciplinary team of professionals working in the field of concrete conservation, and includes a variety of traditional and non-traditional non-destructive, mechanical, chemical, and electro-chemical characterization and diagnostic techniques.